THERAPEUTIC EFFECT OF A UNANI FORMULATION ON HBsAg IN CHRONIC HEPATITIS B: A CASE SERIES - A SIDDIQUI, MOHAMMAD; ANSARI, SHABNAM (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: Chronic hepatitis B (CHB) is a major health concern in terms of its high prevalence, as well as restricted, and costly health care resources in India. The physicians of the Unani system of Medicine have been treating hepatitis since centuries. The purpose of our study was to assess the effect of Unani Formulation in the treatment naÃ¯ve, CHB cases and to collect data to warrant further clinical trials. Methods: We conducted a case series with five patient of CHB, subsequently treated with the Unani formulation. Cases were confirmed with standard hepatitis antigen and viral measurements. The patients were treated for 6 months with measurement of the hepatitis B surface antigen (HbsAg). Results: Loss of surface antigen occurred in the patients and became HbsAg negative within an average 13 weeks of treatment. Discussion: We reviewed the literature related to the Unani formulation used for the treatment in this study. Its constituents have exhibited antiviral, anti-inflammatory, immunomodulatory, hepatoprotective and antioxidant properties, suggesting possible mechanisms of action in the CHB. Conclusion: The preliminary findings indicate the potential therapeutic role of the Unani formulation in the treatment of CHB. Clinical trials based on this Unani pharmacopeal formulation should be conducted to explore the therapeutic potential of this formulation in CHB. Keywords: Chronic hepatitis B, Unani Medicine, Unani formulation, Complementary Medicine, Herbal antivirals, Hepatoprotective, Warme jigar, Viral hepatitis. Â 